EXAGGERATING AND HYPERBOLIC EXPRESSIONS IN NORTHERN KURMANJI WITH REFERENCE TO ENGLISH: A SOCIO- PRAGMATIC APPROACH - ABDULAZIZ, PARWEEN SAADI (Journal of Duhok University, 2022)
The current work deals with exaggerating expressions in the Kurdish language -Northern Kurmanji everyday conversations. This linguistic phenomenon is used for elevating or minimizing entities, characteristics, or actions. It is a figure of speech employed in both language and literature, for the former, the term "exaggeration" is used, while for the latter, the term put into a function is "hyperbole". The concepts expressed in this figure of speech sometimes go beyond logic to represent the extremes in the two ends of a scale in amplifying and/or minimizing ideas. The study concluded that exaggerating and hyperbolic expressions are the same in content, but the former is a property of the language of interaction, while the latter is employed in literature. Politeness and impoliteness, and two ends extremes are manifested by exaggerating expressions. Conventionality and abnormality are the two basic characteristics of exaggeratory expressions; that is, the speaker may use very illogical content to show exaggeration and this is received by the listener in a conventional way that the expressions are common in language despite of their abnormality